2012
DOI: 10.1097/paf.0b013e318267715c
|View full text |Cite
|
Sign up to set email alerts
|

Homicidal Deaths in the Western Suburbs of Paris

Abstract: The aim of our study was to analyze the homicide pattern in the Western suburbs of Paris and its evolution between 1994 and 2008. All autopsy reports regarding homicides from the period January 1, 1994, to December 31, 2008, were retrospectively reviewed. Five hundred eleven homicide cases were selected of 4842 autopsy cases. The following data were recorded: assailants and victims characteristics, crime scene location, homicide motive, cause of death, and victim's postmortem toxicological results. Homicide ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 22 publications
2
6
0
4
Order By: Relevance
“…Finally, we found that about half of the casesfor which we had access to both offender and victim datadisplayed positive toxicology in both parties. That finding is consistent with prior research, whereby a substantial portion of homicides occur following altercations between individuals who consume alcohol together (Cros, Alvarez, Sbidian, Charlier, & Lorin de la Grandmaison, 2012;Wahlsten, Koiranen, & Saukko, 2007).…”
Section: Study Isupporting
confidence: 91%
“…Finally, we found that about half of the casesfor which we had access to both offender and victim datadisplayed positive toxicology in both parties. That finding is consistent with prior research, whereby a substantial portion of homicides occur following altercations between individuals who consume alcohol together (Cros, Alvarez, Sbidian, Charlier, & Lorin de la Grandmaison, 2012;Wahlsten, Koiranen, & Saukko, 2007).…”
Section: Study Isupporting
confidence: 91%
“…Ubijene osobe su znatno ređe ženskog pola, a najčešće su bile žrtve svojih partnera ili razbojništva. Dobro poznata i u sudskomedicinskoj praksi često potvrđena činjenica da su žene mnogo ređe žrtve ubistava u odnosu na muškarce potvrđena je i ovim istraživanjem (1,(16)(17)(18).…”
Section: Diskusijaunclassified
“…kontaktnim ubistvima, pre svega nožem ili nekim tupim oruđem. U francuskoj studiji alkoholisanost je potvrđena čak u 48,5% žrtava ubistava kod kojih je urađena hemijskotoksikološka analiza na alkohol (16), što je znatno veća učestalost nego kod naših žrtava.…”
Section: Diskusijaunclassified
See 2 more Smart Citations